2019
DOI: 10.1186/s13098-019-0430-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low molecular weight urinary proteins at varying time intervals in type 2 diabetes mellitus and diabetic nephropathy patients

Abstract: Background To identify low molecular weight urinary proteins capable of detecting diabetic nephropathy patients which may predict renal alterations at early stages and prevent it from worsening further. Method Three hundred ninety (390) age-matched subjects were divided into 8 groups depending upon duration of diabetes and the severity of renal damage. Urinary proteome profile of all subjects was determined with the help of microfluidic array. Participants with similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Overall, the aforementioned DN markers may reflect the processes of tubular atrophy and tubulointerstitial fibrosis, many of which are important for DN prognosis. Zinc-α2glycoprotein, transthyretin, and AMBP should be especially noted, as their prognostic significance was confirmed in at least two independent studies [71,74,75].…”
Section: Diabetic Nephropathymentioning
confidence: 84%
See 3 more Smart Citations
“…Overall, the aforementioned DN markers may reflect the processes of tubular atrophy and tubulointerstitial fibrosis, many of which are important for DN prognosis. Zinc-α2glycoprotein, transthyretin, and AMBP should be especially noted, as their prognostic significance was confirmed in at least two independent studies [71,74,75].…”
Section: Diabetic Nephropathymentioning
confidence: 84%
“…This seems to be the most important goal for further proteomics research. ↑ [74] Cytoskeletal keratins type I (10) and type 2 (1, 5) ↑ [59] ICAM1 ↑ [60] Metalloproteinase inhibitor 1 ↑ [60] Antitrombin III ↑ [60,63] Adiponectin ↑ [60] α-2-macroglobulin ↑ [63] Ceruloplasmin ↑ [63,65][73] Complement C4a ↑ [63] Haptoglobin ↑ [63][68][75] Prothrombin ↑ [63] LG3 fragment of endorepellin ↓ [64] Glycoprotein 2 ↑ [36] Vasorin ↑ [36] ↓ [65] Epidermal growth factor ↑ [36] CMRF35-like molecule 9 ↑ [36] Protocadherin ↑ [36] Utreoglobin ↑ [36] Dipeptidyl peptidase IV ↑ [36] NHL repeat-containing protein 3 ↑ [36] SLAM family member 5 (CD84) ↑ [36] Aminopeptidase N ↓ [65] Fibulin-5 ↓ [108] YIP1 family member 3 ↓ [108] Prasoposin ↓ [108] Osteopontin ↓ [108] ↑ [110] Small proline-rich protein 3 ↑ [108] ↓ [54] Leucine-rich repeat-containing protein 25 ↑ [54][54] 3340 and 39110 (m/z) ↑ [66] Hepcidin ↑ [67] Protein S89-A9 ↑ [54] α-1 anti-chymotrypsin (SERPINA3) ↑ [68,69] ...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 Through the use of a 2D-DIGE-MALDIQ-TOF strategy and related techniques, Patel et al were able to detect novel DKD-related protein biomarkers in at-risk individuals corresponding to the processes of renal tubulointerstitial fibrosis and tubulointerstitial fibrosis, including apolipoprotein A1, α-1microglobulin, and zinc α-2 glycoprotein. 30 , 31 Guo et al discovered that - 1-antitrypsin - 1-acid glycoprotein, ceruloplasmin, prostate stem cell antigen, APOA4 and other apolipoprotein AIV are prospective protein biomarkers of DKD in 23 diabetic patients and 16 healthy volunteers. 32 Liao et al also observed a significant increase in urinary haptoglobin (Hp) levels in DKD patients, allowing for the more accurate diagnosis and prognostic assessment of individuals with this disease.…”
Section: Urinary Protein Biomarkers Of Dkdmentioning
confidence: 99%